The role of agricultural biodiversity, dietary diversity, and household food security in households with and without children with stunted growth in rural Kenya - M'Kaibi, Florence K. (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.